Transcriptome Analysis Revealed the Early Heat Stress Response in the Brain of Chinese Tongue Sole (Cynoglossus semilaevis) - Wang, Yue; Su, Chengcheng; Liu, Qian; Hao, Xiancai; Han, Shenglei; Doretto, Lucas B.; Rosa, Ivana F. [UNESP]; Yang, Yanjing; Shao, Changwei; Wang, Qian (MDPI, 2024)
As a common influencing factor in the environment, temperature greatly influences the fish that live in the water all their life. The essential economic fish Chinese tongue sole (Cynoglossus semilaevis), a benthic fish, will experience both physiological and behavioral changes due to increases in temperature. The brain, as the central hub of fish and a crucial regulatory organ, is particularly sensitive to temperature changes and will be affected. However, previous research has mainly concentrated on the impact of temperature on the gonads of C. semilaevis. Instead, our study examines the brain using transcriptomics to investigate specific genes and pathways that can quickly respond to temperature changes. The fish were subjected to various periods of heat stress (1 h, 2 h, 3 h, and 5 h) before extracting the brain for transcriptome analysis. After conducting transcriptomic analyses, we identified distinct genes and pathways in males and females. The pathways were mainly related to cortisol synthesis and secretion, neuroactive ligand–receptor interactions, TGF beta signaling pathway, and JAK/STAT signaling pathway, while the genes included the HSP family, tshr, c-fos, c-jun, cxcr4, camk2b, and igf2. Our study offers valuable insights into the regulation mechanisms of the brain’s response to temperature stress.
Keywords: Cynoglossus semilaevis; gene; heat shock; transcriptome